GENETIC DIVERSITY AND POPULATION STRUCTURE OF THE EUROPEAN EEL (ANGUILLA ANGUILLA) IN BALTIC LAKELAND (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Anguilla anguilla (Linnaeus, 1758) is the unique catadromous fish species in the Latvian fauna. The Baltic Lakeland area representing naturally recruited and introduced eels. In recent decades, its population has decreased not only in Latvia, but also in Europe. European eel critically endangered due to overfishing of glass eels, blocking of migratory paths, deaths in HPS turbines, water pollution and diseases and parasites. Only some bodies of water are freely accessible to natural migration of eels in Latvia.Currently, its position has been recognized as being critical, and a range of normative acts have been adopted for its restoration, such as the Regulation EC 1100/2007. The restocking programs of the European eel Anguilla anguilla have been conducted for nearly one century in Latvia.This study provides the first data on population structure of freshwater eels in Baltic Lakeland, for use in eel conservation and management of aquaculture on a regional and/or global scale. By analysing the sequences of the Cyt b gene of mtDNA for individuals caught in locations throughout in Baltic Lakeland, we determined the population genetic structure of A. anguilla in the area. The diversity of haplotypes was studied in ten waterbodies from part of Baltic Lakeland, namely Lake Sīvers, Lake Usmas, Lake Ķišezers, Lake Liepājas, Lake Alūksnes, Lake Rāznas, Lake Vialikija Švakšty, Lake Svir, Lake Myadzyel, Myadzelka river. Additionally, this study investigated the affinity of the Latvian populations to other A. anguilla populations around the world.This is the first report about eel’s population genetic diversity in Baltic Lakeland. Haplotype variation was different in all investigated waterbodies. In current studies seven new unique haplotypes were detected. Eel population in Baltic Lakeland shows quite high genetic diversity and rapid population expansions, which possibly is results of intensive restocking program. Sequences characterized Anguilla rostrata in Lake Alūksnes were detected.